Safety threshold of R-wave amplitudes in patients with implantable cardioverter defibrillator. Issue 20 (13th June 2016) - Lillo-Castellano, J M; Marina-Breysse, Manuel; Gómez-Gallanti, Alfonso; Martínez-Ferrer, J B; Alzueta, Javier; Pérez-Álvarez, Luisa; Alberola, Arcadi; Fernández-Lozano, Ignacio; Rodríguez, Anibal; Porro, Rosa; Anguera, Ignacio; Fontenla, Adolfo; et al.
Abstract : Objective: A safety threshold for baseline rhythm R-wave amplitudes during follow-up of implantable cardioverter defibrillators (ICD) has not been established. We aimed to analyse the amplitude distribution and undersensing rate during spontaneous episodes of ventricular fibrillation (VF), and define a safety amplitude threshold for baseline R-waves. Methods: Data were obtained from an observational multicentre registry conducted at 48 centres in Spain. Baseline R-wave amplitudes and VF events were prospectively registered by remote monitoring. Signal processing algorithms were used to compare amplitudes of baseline R-waves with VF R-waves. All undersensed R-waves after the blanking period (120 ms) were manually marked. Results: We studied 2507 patients from August 2011 to September 2014, which yielded 229 VF episodes (cycle length 189.6±29.1 ms) from 83 patients that were suitable for R-wave comparisons (follow-up 2.7±2.6 years). The majority (77.6%) of VF R-waves (n=13953) showed lower amplitudes than the reference baseline R-wave. The decrease in VF amplitude was progressively attenuated among subgroups of baseline R-wave amplitude (≥17; ≥12 to <17; ≥7 to <12; ≥2.2 to <7 mV) from the highest to the lowest: median deviations −51.2% to +22.4%, respectively (p=0.027). There were no significant differences in undersensing rates of VF R-waves among subgroups. Both the normalised histogram distribution and the undersensing risk function obtained from the ≥2.2 to <7 mV subgroup enabled the prediction that baseline R-wave amplitudes ≤2.5 mV (interquartile range: 2.3–2.8 mV) may lead to ≥25% of undersensed VF R-waves. Conclusions: Baseline R-wave amplitudes ≤2.5 mV during follow-up of patients with ICDs may lead to high risk of delayed detection of VF. Trial registration number: NCT01561144; results.